2016
DOI: 10.3358/shokueishi.57.133
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Azodicarbonamide in Wheat Flour and Prepared Flour Mixes

Abstract: Azodicarbonamide ADA is used in some countries as a flour bleaching agent and a dough conditioner. However, ADA is prohibited for use as a food additive in Japan. Therefore, it is necessary to establish an efficient and sensitive method to determine ADA in wheat flour. A simple and practical procedure to analyze ADA in wheat flour and prepared flour mixes was developed. ADA was extracted from samples by ultrasonication with acetone. ADA in the solution was derivatized with triphenylphosphine TPP . The ADA-TPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Table 2 summarizes the experimental conditions and detection limits of previously published methods. In the proposed method, the LOD of ADC was two to six times lower than those using HPLC in wheat flour products 13,27,28 and that of SEM was 6–25 times higher than those using HPLC 19,22,29 and 10–50 times higher than those using LC–MS/MS 27,32,33 . Additionally, the LOD of HZ was 150 times lower than that using GC 26 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Table 2 summarizes the experimental conditions and detection limits of previously published methods. In the proposed method, the LOD of ADC was two to six times lower than those using HPLC in wheat flour products 13,27,28 and that of SEM was 6–25 times higher than those using HPLC 19,22,29 and 10–50 times higher than those using LC–MS/MS 27,32,33 . Additionally, the LOD of HZ was 150 times lower than that using GC 26 .…”
Section: Resultsmentioning
confidence: 92%
“…The UK Health and Safety Agency has identified ADC as a respiratory sensitizer in the workplace environment, which has resulted in its inclusion in the 2012 REACH regulation of very concerning substances 11 . Australia, the European Union, Japan and Singapore have banned ADC as food additive 10,12–14 . Currently, the United States, Canada, China, and the Republic of Korea allow the use of ADC as an additive in wheat flour but have regulated at a maximum level of 45 mg/kg in wheat flour 14–18…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the linear relationship between ADC concentrations and the number of ADC‐rich pixels in the mixtures. There is a good relationship between the number of ADC‐rich pixels and ADC concentrations in the mixtures, with an R value of 0.9845. The results demonstrated that the method developed in this study can be used for quantitative analysis of ADC additives in flour.…”
Section: Resultsmentioning
confidence: 93%
“…Azodicarbonamide (ADC) is used as a bleaching agent and modifying agent for flour ripening, and can oxidize the cysteine in wheat flour. This increases the flour's glutinosity, the dough's gas retention, and baked goods' flexibility and toughness, and improves the dough's characteristics for shaping and cooking , . However, ADC is extremely unstable and breaks down into trace amounts of semicarbazide during the heating process .…”
Section: Introductionmentioning
confidence: 99%
“…As a wheat flour quality improver, azodicarbonamide (ADA) is used to increase the strength and flexibility of dough and has a certain bleaching effect [Yasui et al, 2016]. ADA acts as an oxidizing agent when wheat flour is stirred into dough with water, and may be transformed into semicarbazide after heat treatment [Becalski et al, 2004;Ye et al, 2011].…”
Section: Introductionmentioning
confidence: 99%